Induction PD-1 inhibitor toripalimab plus chemotherapy followed by concurrent chemoradiotherapy and consolidation toripalimab for bulky locally advanced non-small-cell lung cancer: protocol for a randomized phase II trial (InTRist study) - Wang, Yu; Deng, Lei; Wang, Jianyang; Zhang, Tao; Wang, Wenqing; Wang, Xin; Liu, Wenyang; Wu, Yuqi; Lv, Jima; Feng, Qinfu; Zhou, Zongmei; Wang, Jie; et al. (Frontiers in Immunology, 2024)
Background Immune checkpoint inhibitors (ICIs) have revolutionized the treatment landscape for locally advanced non-small-cell lung cancer (LA-NSCLC), whereas responses to anti-programmed cell death-1 (PD-1) or anti-programmed death-ligand 1 (PD-L1) are heterogeneous. Though consolidation ICI following concurrent chemoradiotherapy (cCRT) improves survival of NSCLC, this regimen is challenging for patients with bulky tumors due to excessive target volumes and radiation-resistant hypoxia during upfront cCRT, leading to higher risk of pneumonitis and inferior local-regional control. Recent trials have demonstrated neoadjuvant ICI brought greater benefit to stage III than stage I-II NSCLC. Our previous study also supported the therapeutic advantage of 2-cycle induction ICI for patients with bulky unresectable stage III NSCLC. In the context of induction immunotherapy, radiotherapy is more likely to exert immune synergistic effects, reverse anti-PD-1 resistance, and activate abscopal immune responses. Prospective trials to determine the efficacy and safety of induction ICI for bulky LA-NSCLC are necessary. Methods This randomized, open-label, two-arm phase II study aims to explore whether 2 cycles of induction anti-PD-1 toripalimab plus chemotherapy can improve progression-free survival (PFS) in bulky LA-NSCLC. Bulky tumors are defined as primary lesion ≥5 cm in greatest dimension or metastatic lymph nodes ≥2 cm in shortest diameter. A total of 50 patients with bulky unresectable stage III NSCLC will be recruited and 1:1 randomized into the experimental arm: 2-cycle induction PD-1 inhibitor toripalimab plus chemotherapy followed by cCRT and consolidation toripalimab; or control arm: 2-cycle induction chemotherapy followed by cCRT and consolidation toripalimab. Patients are stratified by pathology (squamous versus non-squamous). The primary endpoint is PFS. Secondary endpoints are overall survival, overall response rate, disease control rate, duration of response, and incidence of adverse events. Exploratory analyses include PD-L1 expression and liquid biopsy-based biomarker testing, tumor microenvironment profiling at single-cell levels, and quality-of-life assessments. Discussion The InTRist study is the first randomized phase II trial to investigate the feasibility of induction anti-PD-1 toripalimab plus chemotherapy followed by cCRT and consolidation toripalimab in bulky LA-NSCLC, providing novel evidence for the synergistic strategy combining anti-PD-1 blockade with radiotherapy to prolong immunotherapy benefits, overcome resistance, and enhance abscopal immune response. Clinical trial registration ClinicalTrials.gov, identifier NCT05888402.